Topological changes of brain network during mindfulness meditation: an exploratory source level magnetoencephalographic study - Anna Lardone; Marianna Liparoti; Pierpaolo Sorrentino; Roberta Minino; Arianna Polverino; Emahnuel Troisi Lopez; Simona Bonavita; Fabio Lucidi; Giuseppe Sorrentino; Laura Mandolesi (AIMS Neuroscience, 2022)
We have previously evidenced that Mindfulness Meditation (MM) in experienced meditators (EMs) is associated with long-lasting topological changes in resting state condition. However, what occurs during the meditative phase is still debated.